The Use of Ai in Islamic Education and Digital Ethics Instruction for Students at Iai Al-Khairat Pamekasan - Alfiansyah, Alfiansyah (Molang: Journal Islamic Education, 2026)
The growing use of artificial intelligence (AI) in higher education raises serious ethical questions about academic integrity and students’ digital morality. This study examines how students use AI in Islamic Religious Education (PAI) learning and its implications for their digital character (akhlak digital) at IAI Al-Khairat Pamekasan. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participatory observation, and documentation, and analyzed thematically. Findings reveal two patterns of AI use: as a cognitive learning tool and as a task-production tool. Although students generally perceive AI as ethically neutral, a clear gap exists between their normative values and actual practice. AI use has dynamic implications for students’ digital character, simultaneously fostering digital literacy and undermining academic integrity when used without ethical reflection. Students also face three concrete ethical dilemmas: ambiguity about the limits of acceptable AI use, uncertainty about the authenticity of AI-assisted work, and tension between moral responsibility and efficiency pressures. The study concludes that AI does not directly determine the quality of students’ digital character but functions as a testing ground for the internalization of Islamic values in digital contexts. PAI learning therefore needs to integrate digital ethics explicitly and contextually into its practice